Business risk mapping for application of sharing logistic in small medium enterprises - Siti Nuur Fadhillah Mayangsari, Ahmad Danu Prasetyo, Noorhan Firdaus Pambudi, Muhammad Faruq Al-Hadid,; Mulyono, Nur Budi (Opción, 2019)
The aim of the study is to investigate business risk mapping for the application of sharing logistic in small-medium enterprises. This research uses the Analytical Hierarchy Process method for risk measurement by interviewing experts. As a result, we identified 27 risks involved in the logistic sharing model. In conclusion, we found that Consumer risk was considered as the most important risk that should be anticipated in sharing logistic model; followed by Provider risk, Consumer-Provider-Transporter risk, Transporter-External Risk, Consumer-Provider Risk, Consumer-Transporter Risk, Transporter Risk, External Risk, and Provider-Transporter Risk.